Evaluación del sistema de calentamiento eléctrico de agua de uso doméstico y su incidencia en el consumo de energía de la Empresa Eléctrica Quito de la ciudad de Quito en el año 2017. Diseño de programa eficiente de calentamiento eléctrico de agua de uso doméstico para la ciudad de Quito - Soria Riera, Ana María (2017)
The objective of this work is to design a program of efficient electric heating of domestic water that avoids its disorderly effect on the electricity consumption of the Electricity Company of Quito by the implementation of the Efficient Cooking Plan (PEC, acronym in spanish), determining the most suitable equipment both technically and economically for its implementation. An analysis of the habits of use or factor of time variation of electrical heating equipment in the selected primary is carried out to determine the impact on the Company's networks, thus simulating the increase in demand in the primary, determining current and future loadability parameters, so that the criticality can be determined depending on the electric heating equipment used and allows us to determine the overloaded transformers, problems of voltage drops in low-voltage mains and connections. Finally, an economic analysis is carried out which, added to the technical analysis, allows us to suggest an efficient electric heating of domestic water for the city of Quito with the implementation of automated thermostats.